Orientation-controlled nonradiative energy transfer to colloidal nanoplatelets : engineering dipole orientation factor - Erdem, Onur (2020)
We proposed and showed strongly orientation-controlled Förster resonance energy transfer (FRET) to highly anisotropic CdSe nanoplatelets (NPLs). For this purpose, we developed a liquid-air interface self-assembly technique specific to depositing a complete monolayer of NPLs only in a single desired orientation, either fully stacked (edge-up) or fully nonstacked (face-down), with near-unity surface coverage and across large areas over 20 cm2. These NPL monolayers were employed as acceptors in an energy transfer working model system to pair with CdZnS/ZnS core/shell quantum dots (QDs) as donors. We found the resulting energy transfer from the QDs to be significantly accelerated (by up to 50%) to the edge-up NPL monolayer compared to the face-down one. We revealed that this acceleration of FRET is accounted for by the enhancement of the dipole-dipole interaction factor between a QD-NPL pair (increased from 1/3 to 5/6) as well as the closer packing of NPLs with stacking. Also systematically studying the distance-dependence of FRET between QDs and NPL monolayers via varying their separation (d) with a dielectric spacer, we found out that the FRET rate scales with d-4 regardless of the specific NPL orientation. Our FRET model, which is based on the original Förster theory, computes the FRET efficiencies in excellent agreement with our experimental results and explains well the enhancement of FRET to NPLs with stacking. These findings indicate that the geometrical orientation of NPLs and thereby their dipole interaction strength can be exploited as an additional degree of freedom to control and tune the energy transfer rate.